2011
DOI: 10.1186/1743-422x-8-262
|View full text |Cite
|
Sign up to set email alerts
|

Lytic HSV-1 infection induces the multifunctional transcription factor Early Growth Response-1 (EGR-1) in rabbit corneal cells

Abstract: BackgroundHerpes simplex virus type-1 (HSV-1) infections can cause a number of diseases ranging from simple cold sores to dangerous keratitis and lethal encephalitis. The interaction between virus and host cells, critical for viral replication, is being extensively investigated by many laboratories. In this study, we tested the hypothesis that HSV-1 lytic infection triggers the expression of important multi-functional transcription factor Egr1. The mechanisms of induction are mediated, at least in part, by sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 55 publications
3
27
1
Order By: Relevance
“…This observation proposed a connection between neuronal stress and HSV reactivation from latency, suggesting that activation of the Egr-2 from the same stress/stimuli responses may result in LAT suppression and thus play a role in reactivation by abolishing latency. Additional and current studies indicated that during acute infection HSV-1 can directly induce Egr-1 and enhance viral gene expression and replication [2,13,21]. All these results supported the roles of EGR proteins in suppressing latency and promote lytic infection.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This observation proposed a connection between neuronal stress and HSV reactivation from latency, suggesting that activation of the Egr-2 from the same stress/stimuli responses may result in LAT suppression and thus play a role in reactivation by abolishing latency. Additional and current studies indicated that during acute infection HSV-1 can directly induce Egr-1 and enhance viral gene expression and replication [2,13,21]. All these results supported the roles of EGR proteins in suppressing latency and promote lytic infection.…”
Section: Discussionsupporting
confidence: 52%
“…Its expression is found to be correlated to infection by several viruses[2]. These evidences suggest that Egr-1 may play a role in viral gene expression and replication.…”
Section: Introductionmentioning
confidence: 99%
“…The protocol was described previously (19, 47). In short, cell extract was subjected to gel electrophoresis and transferred by iBlot® Gel Transfer Device (Life Technology, Cat#: IB1001).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, a previous report showed that HSV-1 infection activates the ERK/mitogen-activated protein kinase (MAPK) signaling pathway (39). Moreover, it has been shown that HSV-1 lytic infection induces Egr1 in rabbit corneal cells (40). Oxidative stress is capable of initiating the DDR (41) and is reported to enhance the expression of Egr1 (42), and HSV-1 has the ability to induce neuronal oxidative stress (43).…”
mentioning
confidence: 99%